Use of 18F-FDG-PET-CT in glioma surveillance: A single centre experience. (31st January 2018) - Cheserem, Beverly; Kovacs, Bernadett; Bucur, Sorin; Dizdarevic, Sabina; Critchley, Giles
Abstract: INTRODUCTION: Radiological surveillance in glioma surgery is primarily with MRI. Differentiating between disease progression and radionecrosis can be challenging. In our unit, in selected cases when there is suspicion of radiological recurrence, progression or to aid in differentiating progression from radionecrosis, we have augmented our surveillance with 18F-FDG-PET-CT which can highlight areas of metabolic activity which correlate with increased tumour activity. RESULTS: We identified 19 cases of PET imaging for glioma surveillance of whom we could assess 17 notes and images. Mean age was 45.06 (30–67) with male: female ratio 9:8. 15 /17(88.2%) patients had surgery and 2 declined surgery(7 biopsy only, 8 debulk and 2 declined surgery). Initial histology was pilocytic astrocytoma (1), grade II (4, 26.7%), grade III (6, 40%), GBM (3) and non-specific tissue (1). 5 patients had evidence of increased uptake on PET and all showed clinical progression, with only 3 clinically fit for surgery (histology showed 2 recurrence, 1 transformation). 10 patients had no increased uptake on FDG with 4 on on-going surveillance for an average of 8.5 years (7–12), 2 clinically progressed at 2 and 8 years after initial presentation at the point of PET imaging and received palliative chemotherapy, 1 had concurrent inoperable lung cancer and was palliated, 1 patient had transformation from glioma grade II - III, 1 had grade 2 histology, and 1 had only gliotic tissue on re-operation CONCLUSIONS: A positive FDG PET has a positive correlation with disease progression and may be considered as an adjunct test in glioma surveillance.